ANALISIS EKONOMI RUMAH TANGGA TANI DI DAERAH ALIRAN SUNGAI (DAS) SOLO HULU KABUPATEN WONOGIRI - SUPRAPTI SUPARDI (Universitas Sebelas Maret, 2013)
The purpose of this study is to determine the level of household income and the influential variables, determine the level of household food security and standard MIC Upper Solo watershed residents, and to know the pattern of income sources based on farm household income. The study was conducted in the watershed Keduang, covers the districts of: Girimarto, Jatipurno, Jatiroto, Jatisrono, Ngadirojo, Nguntoronadi, Sidoharjo, Slogohimo, and Winton. From each sub-sample is taken of the village passed Keduang watershed streams. From each village is taken 10 samples of poor households and 10 not households.